A carborane-incorporated mononuclear Co(ii) complex showing zero-field slow magnetic relaxation. Issue 99 (25th November 2016) - Tu, Deshuang; Shao, Dong; Yan, Hong; Lu, Changsheng
Abstract : The o -carborane-incorporated Co(ii ) complex shows slow relaxation of magnetization at zero field and a hysteresis loop at 1.8 K. Abstract : An air-stable mononuclear Co(ii ) complex bearing an o -carborane dithiolate ligand has been synthesized which shows slow relaxation of magnetization in the absence of an applied field and a hysteresis loop at 1.8 K. This is the first example of a carborane-incorporated complex that displays SMM properties.